Assessment of neonatal perfusion. Issue 5 (October 2020) - Gupta, Samir; Donn, Steven M.
Abstract: Disorders of perfusion in newborn infants are frequently observed in neonatal intensive care units. The current assessment practices are primarily based on clinical signs. Significant technologic advances have opened new avenues for continuous assessment at the bedside. Combining these devices with functional echocardiography provides an in-depth understanding of perfusion and allows targeting therapy to the pathophysiology rather than monitoring and targeting blood pressure. This change in approach is guided by the fact that perfusion disorders can result from a number of causes and a single management approach might do more harm than good. This approach has the potential to improve long term outcomes but needs to be tested in well-designed trials.